2013
DOI: 10.1057/sj.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

Security officers’ attitudes towards training and their work environment

Abstract: A body of research has examined the nature of security work, legislative efforts and training requirements. Fewer studies, however, have explored security officers' perceptions of the training they received to perform their duties effectively. Although effort has been made to explore how useful the extant of training regime is for security officers in Canada (Manzo, 2009), it is unclear whether such views would hold among security officers in the United States, as both countries have minimal standard requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In addition to their theoretical implications, the findings offer insights into the management of private security personnel. Despite being a key social control agent and their numbers exceeding those of police officers (Nalla and Gurinskaya 2017 ), research suggests that low pay and lack of training diminish PSOs’ job commitment and professionalism and produce negative images of the profession (Cobbina et al 2016 ; Nalla and Heraux 2003 ). To improve public perceptions of private security and instill confidence in PSOs, a systematic effort is needed to educate and train officers to perform their work professionally and in a procedurally just manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their theoretical implications, the findings offer insights into the management of private security personnel. Despite being a key social control agent and their numbers exceeding those of police officers (Nalla and Gurinskaya 2017 ), research suggests that low pay and lack of training diminish PSOs’ job commitment and professionalism and produce negative images of the profession (Cobbina et al 2016 ; Nalla and Heraux 2003 ). To improve public perceptions of private security and instill confidence in PSOs, a systematic effort is needed to educate and train officers to perform their work professionally and in a procedurally just manner.…”
Section: Discussionmentioning
confidence: 99%
“…While PSOs interact with citizens regularly (Nalla and Heraux 2003 ) and share a similar culture (Singh and Kempa 2007 ), motivations, and values with the police (van Steden et al 2015 ), they hold less legal and symbolic power (Joh 2004 ; Mopasa and Stenning 2001 ; Stenning 2000 ) compared to public law enforcement. Additionally, it is widely recognized that PSOs receive very limited to no training (Cobbina et al 2016 ), producing derogatory occupational stereotypes such as “wanna-be-cops” and “rent-a-cop” (Nalla and Heraux 2003 ). These may contribute to the negative public views of private security, which could undermine PSOs’ self-legitimacy.…”
Section: Private Security and Self-legitimacymentioning
confidence: 99%
“…Lewis et al (2005) have used Kegan's (1982Kegan's ( , 1994 theory of identity development to study military cadets entering college, and their results show that the college years represent a time of significant developmental change. Cobbina, Nalla and Bender (2016) have explored security officers' perceptions of the training they received to perform their duties effectively. Among other things, they have found that security officers perceived a lack of adequate training to perform their tasks effectively, and they highlighted the importance of systematic and standardised training.…”
Section: Officer Identitymentioning
confidence: 99%
“…The public often characterizes the security guard as untrained and ill-prepared caricatures of the public police (Cunningham & Taylor, 1985; Mulone, 2013; Shearing & Stenning, 1983). The idea that security guards are untrained is also professed by security industry leaders who routinely call for more training to further improve and legitimize the private security industry (Cobbina, Nalla, & Bender, 2013; Thumala et al, 2011). Private security guards have the potential for abuses of power, and when this is coupled with the relatively low educational standards to enter into the occupation, it is logical to see why both the public and security professionals have ambivalent feelings about the legitimacy of the security industry.…”
Section: Statutory Regulationsmentioning
confidence: 99%